Effect of averaging period on wind resource assessment for wind turbine installation project at UNITEN - Roslan E.; Mohamed H.; Chan L.; Isa M.R. (American Institute of Physics Inc., 2023)
Assessing the wind resource available at a particular site is the initial step of determining the feasibility of a wind turbine installation project. Several methods are frequently used to assess wind resource at a particular site, such as using wind map, local site measurement and measure-correlate-predict. A certain degree of measurement at site is needed for the final two methods. Wind speed data is usually measured and collected at a certain frequency or sampling rate, based on the resolution of the measurement device used. This data is then averaged at a certain period, depending on the standards used or its application. This research investigates the effect of having different averaging period when processing the raw wind speed data on the estimated power and energy potential of a wind turbine installation project at Universiti Tenaga Nasional (UNITEN), Malaysia. Results have shown that different averaging periods 2-minute and 10-seconds have 27.15% and 54.3% difference respectively to hourly averaged data in terms of energy yield estimation. These differences can affect a feasibility study of a wind turbine project. 2018 Author(s).